DESECURITISATION OF BRUNEI’S CHINA SHARIA PENAL CODE ON THE PUNISHMENT TOWARDS LGBITQ - Adityo Darmawan, Maya Bofa, Felian (Hamdard Islamicus, 2020)
This paper aims to explain policy changes of Brunei’s Sharia Penal Code (SPC) regarding punishment towards the LGBTIQ community. The SPC was quietly announced in December 2018, which initially would have been implemented in April 2019. However, in May 2019, the Sultan announced that his government would not implement the SPC. The policy changes of Bolkiah will be analyse d by a qualitative method with rational choice and Securitisation theory. Data will be collected through secondary data from books, journals, articles, and other sources. This research found that the policymaking was initiated as a process of Securitisation but then the government decided upon desecuritisation theory on that issue, which was affected by the global pressures. Such pressures could bring huge economic loss to both the Brunei government and Bolkiah himself, for example, by boycotting around nine properties owned by Bolkiah and those related to the Brunei Investment Agency. That process is reflected through a negotiation among security actors on which sector should be prioritised.